Effect of adding organic and mineral fertilizers on productivity and quality of jew's mallow leaves - Aboud, F.A. (2007)
The research was conducted during 2005 and 2006 in Almriyaia. Delr Ezzor to determine the effects of adding organic and mineral fertilizers on the contents of NO2 and NO3 in Jew's mallow leaves. Results show that absence of NO2 In first and second harvests tor all studied treatments was obvious. While. using urea and cow manure yielded high productivity of leaves and low content of NO3. The treatment of balanced solvable NPK was the second in productivity of leaves and contained low concentration of NO3. On the ottIer hand, using NH4 NO3 and (NH4)2 SO4, resulted in low yield and increased content of NO3 in Jew's mallow leaves.
Includes references.
Summary in Arabic.
1
Keywords: Tossa jute -- Syria; Tossa jute -- Fertilizers; Fertilziers